An Elephant Foot Analogy: Design and Development of Landing Gear - A. Swamy; T. A. Zebenay (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study was to investigate, analyze, and develop a landing gear mechanism. To support the analysis, we used an elephant foot analogy. Elephant, especially African elephant, is the largest terrestrial mammals living on the planet. Having enormous size and distinctive weight make them classified as one of the significant surviving species. The project mainly focused on the use of elephant foot analogy for understanding the reduction of asphalt deformation. The deformation was tested by reducing the simulated stresses. The final solution mimics elephant foot stress absorption carrying capacity, in which this can be modeled for the modified landing gearscould demonstrate the use of BIM for bridge rehabilitation.